2005
DOI: 10.1111/j.1365-2559.2005.02193.x
|View full text |Cite
|
Sign up to set email alerts
|

Microvessel density for melanoma prognosis

Abstract: Microvessel assessment of primary melanoma using the Chalkley score technique provides reliable prognostic information on the risk of recurrence of the tumour, particularly for melanomas deeper than 2 mm. It remains to be seen whether this methodology can predict response to novel anti-angiogenic therapies currently entering trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 30 publications
3
32
0
1
Order By: Relevance
“…The Chalkley vessel counting technique is an objective, easy, and reproducible method and provides both a quantitative and qualitative assessment. 19 The study by Hansen et al 22 demonstrated prognostic significance of tumor vascularity in breast carcinomas, when assessed by the Chalkley counting technique in contrast to assessing microvessel density as originally presented by Weidner et al 12 The Chalkley method therefore was adopted in this study.…”
Section: Discussionmentioning
confidence: 97%
“…The Chalkley vessel counting technique is an objective, easy, and reproducible method and provides both a quantitative and qualitative assessment. 19 The study by Hansen et al 22 demonstrated prognostic significance of tumor vascularity in breast carcinomas, when assessed by the Chalkley counting technique in contrast to assessing microvessel density as originally presented by Weidner et al 12 The Chalkley method therefore was adopted in this study.…”
Section: Discussionmentioning
confidence: 97%
“…As in large-scale studies of breast carcinoma, exhibiting a significant and independent prognostic value for survival, Depasquale and Thompson [38] concluded that tumor microvessel counts, by the Chalkley technique, were related to a risk of recurrence in melanomas thicker than 2.0 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Applying this counting technique to microvessels makes it possible to achieve greater correspondence between the points on the graticule and the vascular lumens, thus reflecting not just the total number of microvessels, but the relative area they occupy [38]. This method is considered more objective and has been indicated as the most powerful predictive factor of the prognosis of many neoplasms [39], as in studies of breast carcinomas showing a significant and independent prognosis for survival.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, to become clinically relevant, a tumor requires persistent neovascularization for its growth and survival (30). Neoplastic vessel density is correlated with an adverse prognosis in many types of adult and pediatric solid tumors (31,32).…”
Section: Discussionmentioning
confidence: 99%